Pupuk Organik dari Limbah Pabrik Gula Madukismo dengan Starter Mikrobia Pengurai Untuk Menambah Kandungan N, P, K - Ratna Sri Harjanti (CHEMICA: Jurnal Teknik Kimia, 2017)
AbstrakÂ Blotong is sugar mill waste slude in the form of dark, often dumped, causing pollution and odor. Blotong produce about 3,8 % of cane milled by a sugar factory unit. While vinasse is waste water generated from the process of making alcohol. In the process of making one liter of alcohol will produce as much as 13 liters of vinasse. Vinasse contain many elements K, while blotong contains a lot of elements of N, P, dan Ca. This allows for composting blotong with the addition of vinasse to produce organis fertilizer. Blotong and vinasse may be seen in the PG Madukismo.Organic fertilizer through composting mixture of blotong and vinasse using microbial starter EM-4 and X-Compost can be done easily in the home environment. To determine the optimum process conditions to produce organic fertilizer, need to be varied ratio of blotong and vinasse. Composting reaction carried out for thirty days with observed in temperature and pH. Further analysis of N, P, K and C/N ratio.Based on the results obtained, the use of starter microbes X compost more prospective than using starter microbes EM-4. The compost produced by the starter microbes X-compost contains N, P, K which is much higher than the compost produced by the starter micobes EM-4. As for the addition of vinasse, will give optimum results in the addition of vinasse 25% of the weigth of blotong.Â Keywords: blotong, vinasse, compost, microbe